IMPLEMENTATION OF EVENT MANAGEMENT IN COMMUNITY PARTICIPATION IN SUKAJADI VILLAGE, BOGOR REGENCY - Sugih Setiawan, Aditya; Rahmaniyah Utami, Nisa; Dinitri, Seruni; Pratiwi Batubara, Rima; Bagaskara, Suliwa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Bogor Regency is one of the favorite destinations in the Greater Jakarta area. One of the tourism developments in the countryside is the Sukajadi Village area. The form of development of the Sukajadi village area that can be done is community participation in implementing an event. In addition, with the existence of an event, the promotion of Sukajadi village as an alternative tourist village can be maximized. The method of implementing event management in Sukajadi village is done by involving the participation of students and the community participation in designing these activities. The implementation plan starts from the Event planning stage by determining the theme that will be raised in the event. The participation used in this "reunite people with nature" activity is a form of symbolic community participation (tokenism) including Placation, Consultation, and Informing.